Nitric oxide (NO) generation during vegetative/generative transition of the apical meristem in wheat - Kolbert, Zsuzsanna (Acta Biologica Szegediensis, 2011)
The phase transition from vegetative to reproductive development of the shoot apical meristem (SAM) is a critical event during the life cycle of seed-propagated plants. Nitric oxide (NO) as a general plant signal plays a role during growth and development and under biotic and abiotic stress conditions. In this study, apical meristems of spring wheat (Triticum aestivum L. cv. Thaifun) were isolated during their development and NO was detected by DAF-FM using a fluorescent microscope. To test the NO specificity of DAF-FM, in vivo and in vitro experiments were also carried out. In vegetative apices NO level was very low and it significantly enhanced during transition (in the „double ridge” phase). After transition, NO level decreased and proved to be low in the generative phase (11th-13th week). Our results show that DAF-FM is a suitable and specific indicator of NO. The significant increase in NO level during the vegetative/generative transition of wheat SAM suggests its regulatory function.